Mini Economica Media Komunikasi Ilmu Ekonomi : Analysis of Asset Growth Anomaly On Cross-Section Stock Returns : Evidence From Indonesia Stock Exchange - Iqbal, Muhammad, Wibowo, Budi (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
Assorted types of market anomalies occur when stock prices deviate from the prediction of classical asset pricing theories. This study aims to examine asset growth anomaly where stocks with high asset growth will be followed by low returns in the subsequent periods.